Synthesis and Crystal Structure of Novel Macrocyclic Molecule: [Ni(C26H20N6S2)Cl2]2(H2O)2 - Dong, Hua-Ze; Pi, Zong-Xin; Hu, Jing; Bi, Jian-Hong (Asian Journal of Chemistry, 2013)
A novel Ni(II) complex with the formula ([Ni(C26H20N6S2)Cl2]2(H2O)2) was synthesized by pyridyl-pyrimidinyl dithioethers and NiCl2, as the dinuclear [2+2] macrocyclic motif. The present compound shows six-coordinate core (NiN4Cl2), which is distorted octahedral geometry and led to a novel 3D supramolecular complex by the intermolecular hydrogen bonds interactions among the adjacent dinuclear units. The crystal is monoclinic crystal system, space group P21/c with unit cell parameters: a = 11.9071(11) Å, b = 11.7096(11) Å, c = 19.2484(18) Å, a = 90.00º, b = 101.886(2)º, g = 90.00º, V = 2626.2(4) Å3, Z = 2, Mr = 1256.45, Dc = 1.589 g/cm3, μ = 1.135 m m-1, F(000) = 1288.0, R = 0.0633, wR = 0.1718 for 2869 reflections with I > 2s(I).